2017
DOI: 10.1007/s11524-017-0167-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a Temporary Urban Pop-Up Park on Physical Activity and Other Individual- and Community-Level Outcomes

Abstract: Physical inactivity is a known risk factor for obesity and a number of chronic diseases. Modifying the physical features of neighborhoods to provide residents with equitable and convenient access to spaces for physical activity (PA) is a promising strategy for promoting PA. Public urban recreation spaces (e.g., parks) play an important role in promoting PA and are potentially an important neighborhood element for optimizing social capital and liveability in cities. Most studies examining the effects of park av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 44 publications
(53 reference statements)
0
28
0
2
Order By: Relevance
“…Pop-up parks are by definition small and temporary, and are located in areas typically reserved for cars (parking lots, streets) (90). A recent study in Los Altos, CA, USA, found that a small, urban pop-up park attracted a large number of multigenerational users (91). High levels of PA in the pop-up park were observed among youth.…”
Section: Physical Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Pop-up parks are by definition small and temporary, and are located in areas typically reserved for cars (parking lots, streets) (90). A recent study in Los Altos, CA, USA, found that a small, urban pop-up park attracted a large number of multigenerational users (91). High levels of PA in the pop-up park were observed among youth.…”
Section: Physical Environmentmentioning
confidence: 99%
“…High levels of PA in the pop-up park were observed among youth. Among users, the presence of the pop-up park was associated with less screen time, and with more time spent at a park, outdoors, and in the downtown central business district of Los Altos (91). Pop-up parks represent a promising strategy for communities with limited space for public recreation facilities, both to promote PA, as well as to improve social capital and quality of life through the revitalization of urban settings.…”
Section: Physical Environmentmentioning
confidence: 99%
“…Moreover, by examining patterns of PUP use through robust direct observation, Salvo et al . () showed that PUPs triggered beneficial changes in time‐allocation patterns among users, including a reduction in screen time and an increase in overall time spent outdoors; we believe that this is the first, and thus far only, published work to provide empirical evidence of the social benefits of PUPs.…”
Section: Potential Social Benefits Of Pupsmentioning
confidence: 74%
“…Related studies on the design of pocket parks highlighted the key role of particular design elements in stimulating social interactions and mental restoration, from varying the amount and arrangement of both natural (eg vegetation [including flowers], water) and human-made (eg seating arrangements) elements (Nordh and Ostby 2013;Peschardt et al 2016). Moreover, by examining patterns of PUP use through robust direct observation, Salvo et al (2017) showed that PUPs triggered beneficial changes in time-allocation patterns among users, including a reduction in screen time and an increase in overall time spent outdoors; we believe that this is the first, and thus far only, published work to provide empirical evidence of the social benefits of PUPs.…”
Section: Potential Social Benefits Of Pupsmentioning
confidence: 99%
“…In residential areas, neighborhood public parks and leisure spaces can encourage socialization and physical activity [17][18][19]. Such parks are located in accessible, prominent areas which promote active transport and provide for the recreational needs of a local community for informal passive and active recreation and leisure opportunities, they also provide an important focal point for social interaction [20].…”
Section: Encouraging Socialization and Physical Activity Through Publmentioning
confidence: 99%